IJCM_374A: Parental perspectives on the MR vaccination campaign in Mangaluru insights from government mandates: A cross-sectional study - Rekha T; Ahuja Prerna; Dixit Yashi; Jaiswal Akhil; Mathur Saksham; Reddy Sweta; Unnikrishnan Bhaskaran; Mithra Prasanna; Kumar Nithin; Holla Ramesh (Wolters Kluwer Medknow Publications, 2024)
Background: Measles is the leading cause of child mortality in India. MR vaccine provides immunity against measles & rubella and was offered in 2 doses - 9 completed months and 16-24 months of age. This study aims to assess the awareness among the parents of children (aged 9 months - 2 years) in Mangalore about the presence and the risks associated with measles and rubella and to determine how the parents perceive the MR vaccination drive launched by the Government of India in terms of its necessity and safety of their children. Methodology: This cross-sectional study was conducted among 188 parents of children between the age of 9 months - 2 years from health centers in Mangalore. The data was collected using a semi-structured questionnaire- consisting of 3 sections: 1) Socio-demographic information of study participants 2) Knowledge-based questions on measles and rubella 3) Perception of MR vaccination drive. Data was analyzed using SPSS version 21. Appropriate statistical tests were applied, and results were interpreted. Results: The study population mainly comprised individuals aged 23-30 years (37.8%), predominantly females (65.3%), they prefer government hospitals for child vaccination (71.5%), resulting in 73.1% of children being meeting national immunization targets by age 2 years. Only 33,4% of the parents have understanding of Measles and Rubella diseases and associated risks. Parents exhibit awareness of the MR vaccine drive (Overall 86.7%) through newspapers (46.0%) and schools (39.0%), supporting its mandatory status (76.0%). Doctors play a crucial role in addressing parental queries (59.5%) regarding the MR vaccination drive. Conclusions: Parents show awareness of the MR Vaccination Drive but lack understanding of Measles and Rubella diseases and associated risks. Despite limited knowledge, parent's express receptiveness to the MR Vaccination, drive for their children's safety, with some showing interest in learning more about the vaccine and diseases.